2017
DOI: 10.1007/s00394-017-1488-x
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy in socioeconomic status does not fully explain the variation in diet quality between consumers of different coffee types

Abstract: Coffee consumers' different preferences towards coffee type and additive usages reflected significant variations in their diet quality, even after adjustment of SES. Therefore, future epidemiological studies should consider separating coffee drinkers according to their habitual consumption of different types of coffee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…Our results agree with an Australian dietary survey conducted in 2011 to 2012 ( n = 6,232). Habitual consumers of espresso or ground coffee lived in households with higher SES and consumed more dietary caffeine than those who consumed mix coffee or instant coffee, or those not consuming coffee (50). Espresso and ground coffee consumers were also more likely to have a bachelor’s degree or higher than other groups (50), which is analogous to our findings with the SEIFA descriptors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results agree with an Australian dietary survey conducted in 2011 to 2012 ( n = 6,232). Habitual consumers of espresso or ground coffee lived in households with higher SES and consumed more dietary caffeine than those who consumed mix coffee or instant coffee, or those not consuming coffee (50). Espresso and ground coffee consumers were also more likely to have a bachelor’s degree or higher than other groups (50), which is analogous to our findings with the SEIFA descriptors.…”
Section: Resultsmentioning
confidence: 99%
“…Habitual consumers of espresso or ground coffee lived in households with higher SES and consumed more dietary caffeine than those who consumed mix coffee or instant coffee, or those not consuming coffee (50). Espresso and ground coffee consumers were also more likely to have a bachelor’s degree or higher than other groups (50), which is analogous to our findings with the SEIFA descriptors. Our findings also support cohort studies which find higher caffeine consumption among higher SES adolescents (51) and adults (52).…”
Section: Resultsmentioning
confidence: 99%
“…A previous Polish study showed that individuals who consumed nuts had better dietary habits than individuals who did not consume nuts [45]. Moreover, the Australian Health Survey indicated that habitual consumers of espresso and ground coffee have a higher socioeconomic status than consumers of coffee mixes and instant coffee and non-consumers of coffee [46].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, our results provided a possible explanation for the contradicting findings in previous studies, in which coffee was found to be protective against T2D (1,2) while capable of inducing acute glucose intolerance (3,4,23) at the same time. This is especially the case when milk and sugar consumption with coffee is a common practiceit was estimated that more than 80 % of participants in a nationally representative Australian cohort added either milk or sugar, or both, into their coffee (24) , while this habit was also observed in more than 50 % of the participants in an American National Health Examination (25) . In order to validate the findings of the present study in large-scale population surveys, data on milk and sugar usage together with coffee consumption should also be collected in future studies.…”
Section: Discussionmentioning
confidence: 99%